Fascism, uncensored - Heywood, Paolo (Terrain: anthropologie & sciences humains, 2025)
This article describes the afterlife of the 1952 Scelba Law in Italy, which forbids “apologias” for the fascist regime, and its chequered history of application. Intended to censor, amongst other things, speech directed towards the reconstitution of an Italian fascist party, fascist propaganda, and fascist demonstrations, the Scelba Law has been sparingly and inconsistently applied. This is particularly evident in the village of Predappio, Mussolini’s home town, and one of Italy’s premier sites of neo-fascist tourism. This article explores the ways in which the pointed absence of censorship in Predappio constitutes an intervention in a wider set of debates surrounding how to identify “fascism” as an object. It thus highlights the value of examining not only the productivity of censorship as a practice and vocation but also the potentially productive force of abstaining from censorship.